Understanding jurisprudence : an introduction to legal theory - Wacks, Raymond (Oxford University Press, 2005)
"Understanding Jurisprudence provides a lucid introduction to the absorbing and challenging field of legal theory. Without avoiding the complexities and subtleties of the subject, Raymond Wacks provides an illuminating guide to the central questions of legal theory."--Jacket